Upaya Meningkatkan Hasil Belajar Pada Pembelajaran Matematika Materi SPLDV Dengan Menerapkan Model Pembelajaran Improve - Millah, Siti Izzatul; Purnomo, Bambang; Faizin, Affan (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
Learning results are the results that achieved by someone after learning activities and the assessment achieved by someone to determine the extent to which the materials or material taught has accepted the students. However, based on experience researchers for teaching in SMK Satya Widya Surabaya, students mathematic learning result who taught by the method konventional such as the method is quite low. So that's why, it is necessary learning alternative model can enhance learning result. One of alternative that can be used is IMPROVE learning model based it will be used IMPROVE learning model in a class action research, the results of research that by using the IMPROVE learning model can increase the understanding of the concept of student so that the student results also increase. Overall after the application of a class action cycle 1 to cycle 2 with learning model improv on material SPLDV can increase the understanding of the concept of so that the student learning result in grade X aph 4 SMK "pariwisata" Satya widya Surabaya also increase. Keywords: IMPROVE Learning Model, Class Action Research, The Results Learning